Supramolecular networks stabilise and functionalise black phosphorus - Vladimir V. Korolkov (Nature Portfolio, 2017)
Few-layered black phosphorus has been exploited in transistors and other devices, but its poor stability under ambient conditions remains problematic. Here, a UK-Swiss collaboration show that a monolayer-thick supramolecular hydrogen-bonded network can protect a black phosphorus surface for over a month.